The role of the South African national lexicography units in the planning and compilation of multifunctional bilingual dictionaries - Mongwe, Mkomati John (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Afrikaans and Dutch))—University of Stellenbosch, 2006.